Serum magnesium levels in healthy dogs submitted to the administration of cisplatin with fluid therapy - Calpa Oliva, Carlos Alfredo; Daleck, Carlos Roberto [UNESP]; Teotonio de Castro, Joao Humberto [UNESP]; de Nardi, Andrigo Barboza [UNESP] (Univ Nacional Autonoma Mexico Facultad Medicina Veterinaria Zootecnia, 2011)
Cisplatin is an antineoplastic drug that is used to treat carcinomas and osteosarcomas in dogs. However, it can cause kidney damage which in turn leads to the loss of electrolytes. Concentration of magnesium was evaluated in the blood serum of eight dogs that had undergone therapy with cisplatin. The dogs were divided into two groups. Group 1 was supply with cisplatin (70 mg/m(2), iv) and to prevent nephrotoxcity, saline solution at 0.9% was administered (25 ml/kg/hour, iv in three hours). The animals in Group 2 were not supplied with cisplatin. There was no significant difference (P < 0.05) between the two groups and the results obtained indicated that the protocol used for Group 1 did not cause changes in the serum concentrations of magnesium. Therefore, it can be concluded that the administration of cisplatin does not cause variations if it is combined with the fluid therapy.
Keywords: Cisplatin; FLUID THERAPY; Chemotherapy; Magnesium; Electrolytes